PERAN LINGKUNGAN KELUARGA PADA PENGGUNAAN GADGET TERHADAP GEMAR MEMBACA SISWA SEKOLAH DASAR - Jennifer Del Amore, Maria; Heru Purnomo (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This research explores how the family environment influences gadget use and its effect on the reading interest of elementary school students. A descriptive qualitative method was employed, utilizing interviews, observation, and documentation as data collection techniques involving both parents and children. Data were gathered through questionnaires distributed to 12 elementary school students. The findings show that parental involvement in managing screen time and controlling digital content significantly contributes to the development of children's reading habits. Families that model reading behavior, provide access to both printed and digital reading resources, and restrict non-educational gadget usage tend to raise children with stronger reading interests. In contrast, unregulated gadget use often leads to screen dependency and detachment from literacy-related activities. This study highlights the need for strong cooperation between families and schools to promote family-centered digital literacy